High temperature behaviour of ambient cured alkali-activated materials based on ladle slag - Murri, A.; Rickard, William; Bignozzi, M.; Van Riessen, Arie (Pergamon- Elservier, 2013)
This paper investigates the thermal properties of alkali activated materials (AAMs) made from ladle slag, a by-product from electric arc furnaces. AAMs have the potential to exhibit improved durability in high temperature environments over conventional materials such as ordinary Portland cement due to a reduced concentration of hydrated phases in their structure. A series of samples with varying compositional ratios was synthesised from a combination of ladle slag and metakaolin or ladle slag and fly ash. Ambient cured AAMs of moderate compressive strengths (between 11 and 46 MPa) were achieved. Samples were exposed to temperatures up to 1000 °C and analysed for residual strength, thermal expansion, phase and microstructural changes. The ladle slag and fly ash based AAMs exhibited superior strength gains and better thermal stability than the ladle slag and metakaolin based AAMs believed to be due to unstable C–A–S–H phases formed in the latter group of samples.